Pengembangan Alat Evaluasi Hasil Belajar Mata Pelajaran Pendidikan Agama Islam Berbasis Taksonomi Bloom Dua Dimensi - Yulianti, Yulianti (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2016)
The assessment tools of the subject of Islamic Religious Education (PAI) used in SMPIT At-Taqwa Surabaya refer to textbooks provided by the school. The teachers do not pay attention to the level of two dimensions: namely, cognitive processes and knowledge that are summarized in the word â€œBloom operational taxonomic revisionâ€. The development process of this assessmentis based on the model of development according to Bloom which is modified into five phases: namely, initial investigation, design, realization, testing, and implementation. The results of this assessment development state that theassessment tools fulfill the valid, reliable and practical aspects. The assessment of learning result of PAI by using Bloom`s Two Dimension Taxonomy got a score 3.29 which is categorized very valid. The validity coefficient of item1 to 6 is categorized as high. The reliability coefficient of the test question description developed is 1.019524 with the category of very high.